The Warburg effect promoted the activation of the NLRP3 inflammasome induced by Ni-refining fumes in BEAS-2B cells. (August 2020) - Wang, Rui; Wang, Sheng-Yuan; Wang, Yue; Xin, Rui; Xia, Bing; Xin, Ye; Zhang, Tong; Wu, Yong-Hui
Nickel (Ni) is a known human carcinogen that has an adverse effect on various human organs in occupational workers during Ni refinement and smelting. In the present study, we used real-time polymerase chain reactions, Western blot analysis, and a lactate production assay to investigate whether an increase in the NLRP3 inflammasome induced by Ni-refining fumes was associated with the Warburg effect in BEAS-2B cells, a nonmalignant pulmonary epithelial line. Exposure to Ni-refining fumes suppressed cell proliferation and increased lactate production compared with those in an untreated control group in a dose- and time-dependent manner. Ni-refining fumes induced the Warburg effect, which was observed based on increases in the levels of hypoxia-inducible factor-1α, hexokinase 2, pyruvate kinase isozyme type M2, and lactate dehydrogenase A. In addition, Ni-refining fumes promoted increased expression of NLRP3 at both the gene and protein levels. Furthermore, inhibition of the Warburg effect by 2-Deoxy-d -glucose reversed the increased expression of NLRP3 induced by Ni-refining fumes. Collectively, our data demonstrated that the Warburg effect can promote the expression of the NLRP3 inflammasome induced by the Ni-refining fumes in BEAS-2B cells. This indicates a new phenomenon in which alterations in energy production in human cells induced by Ni-refining fumes regulate the inflammatory response.